New Rhetoric and the Socio-Rhetorical Method: As a Modern Approach to Biblical Literary Criticism - Padilla, José David (Advances in Social Sciences Research Journal, 2020)
The new rhetoric studies the discursive practices present in a text and tries to understand them as a literary method to persuade a specific audience to accept a new law or change their behavior, assuming a worthy moral, philosophical or religious truth. The new rhetoric covers the literary or rhetorical analysis of discourse while analyzing the elements proper to the social and cultural milieu of its intended audience. The aid of the human sciences, especially cultural anthropology and the sociology of religion, is necessary to capture better the world the loci of the speaker and the audience of the text. The method, which combines social and anthropological analysis with the new rhetorical analysis, is called social rhetoric. The social rhetoric analysis aims to hit the socio-cultural context in which the texts were conceived, especially when the text does not give any clues of it. In Biblical interpretation, these two forms of literary analysis will help to understand the relationships existent between the author of a discourse and its readers (the intended audience). Such an approach will not only study the social history and social aspects where the books of the Bible were born, but will also see the rhetoric of the texts as an essential component of the text’s social, political, cultural, and ideological context. After all, the Word of God became flesh and dwelt in a particular culture, with a specific language and in a precise historical time.